Resonance fatigue testing on high-strength self-compacting concrete. (March 2021) - Thomas, C.; Sainz-Aja, J.; Setien, J.; Cimentada, A.; Polanco, J.A.
Abstract: Concrete structures are increasingly affected by fatigue damage, while new slender building structures with greater mechanical requirements make it necessary to deepen knowledge of their behaviour under fatigue loading. In this research, high-strength plain concrete was studied under two different frequencies of cyclic compressive stress. Wöhler curves were obtained in two different ways, on the one hand, applying a uniform frequency of 10 Hz and, on the other hand, applying the specimen resonance frequency. The results show two different types of behaviour. A reduction in fatigue life was observed in those concretes tested at very high frequency. When loads were applied at resonance frequency, they did not seem to modify the breaking mechanisms of the concrete subjected to fatigue. Highlights: Analysis review of concrete behavior under fatigue. Influence of the frequency of fatigue on fatigue life. Relationships between statical and dynamic properties. S–N curve of concrete obtained at high frequency. Resonance fatigue frequency testing.